2019
DOI: 10.1111/cge.13620
|View full text |Cite
|
Sign up to set email alerts
|

MAGEL2‐related disorders: A study and case series

Abstract: Pathogenic MAGEL2 variants result in the phenotypes of Chitayat‐Hall syndrome (CHS), Schaaf‐Yang syndrome (SYS) and Prader‐Willi syndrome (PWS). We present five patients with mutations in MAGEL2, including the first patient reported with a missense variant, adding to the limited literature. Further, we performed a systematic review of the CHS and SYS literature, assess the overlap between CHS, SYS and PWS, and analyze genotype‐phenotype correlations among them. We conclude that there is neither a clinical nor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 40 publications
(153 reference statements)
1
52
0
3
Order By: Relevance
“…Yet, since our cohort was initially suspected of having PWS, an inclusion bias may be present. It was recently reported that Chitayat-Hall syndrome was also caused by pathogenic variants in MAGEL2 [12,14]. GH deficiency, which is a characteristic of this syndrome, was found in all three cases in whom GH was evaluated.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…Yet, since our cohort was initially suspected of having PWS, an inclusion bias may be present. It was recently reported that Chitayat-Hall syndrome was also caused by pathogenic variants in MAGEL2 [12,14]. GH deficiency, which is a characteristic of this syndrome, was found in all three cases in whom GH was evaluated.…”
Section: Discussionmentioning
confidence: 73%
“…Although it was reported that SYS patients have a higher prevalence of ASD [3,5,9], this could not be evaluated due to the severe intellectual disability in most of our patients. Previous studies report that among adolescent patients with SYS, the proportion of those who presented with hyperphagia and obesity was low, unlike that of patients with PWS, and many of those presented with ASD [9,14]. In our study, it was difficult to evaluate patients in these respects because we could only observe two patients until puberty; however, we identified some patients without hyperphagia, obesity, or the personality characteristic of PWS.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations